Bioinformatics analysis of key genes and pathways for hepatocellular carcinoma transformed from cirrhosis. Issue 25 (June 2017) - He, Bosheng; Yin, Jianbing; Gong, Shenchu; Gu, Jinhua; Xiao, Jing; Shi, Weixiang; Ding, Wenbin; He, Ying
Abstract: Objective: We aimed to identify some pivotal genes and pathways for hepatocellular carcinoma (HCC) transformation from cirrhosis and explore potential targets for treatment of the disease. Methods: The GSE17548 microarray data were downloaded from Gene Expression Omnibus database, and 37 samples (20 cirrhosis and 17 HCC samples) were used for analysis. The differentially expressed genes (DEGs) in HCC tissues were compared with those in cirrhosis tissues and analyzed using the limma package. Gene ontology-biological process and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analyses were performed using ClueGO and CluePedia tool kits, and the key KEGG pathway was analyzed using the R package pathview. The regulatory factor miRNA of DEGs was extracted from 3 verified miRNAs-target databases using the multiMiR R package. Moreover, a protein-protein interaction (PPI) network was constructed using the Cytoscape software. Results: DEGs including cyclin-dependent Kinase 1 (CDK1), PDZ-binding kinase (PBK), ribonucleotide reductase M2 (RRM2), and abnormal spindle homolog, and microcephaly-associated drosophila (ASPM) were the hub proteins with higher degrees in the PPI network. The cell cycle pathway (CDK1 enriched) and p53 signaling pathway (CDK1 and RRM2 enriched) were significantly enriched by DEGs. Conclusion: CDK1, PBK, RRM2, and ASPM may be key genes for HCC transformation from cirrhosis. Furthermore, cell cycle and p53 signaling pathways may play vital mediatory roles; CDK1 may play crucial roles in HCC transformed from cirrhosis via cell cycle and p53 signaling pathways, and RRM2 might be involved in HCC transformed from cirrhosis via the p53 signaling pathway. Abstract : Supplemental Digital Content is available in the text